REPUBLICA MOLDOVA ÎN CONTEXTUL INTEGRĂRII EUROPENE - MOLDOVANU, bibliotecar principal, Filiala de Arte „T. Arghezi”, Anastasia (BIBLIOPOLIS, 2020)
The social and political events that have evolved in our country have spurred political decisions made by government and, especially the public opinion to redefine clearly the position towards the adhesions to the European vector. The 2015 is considered the European integration Year in all spheres of activity - economic, social, political, cultural. For national libraries the idea of integration is related to knowledge and information, to the European cultural and performance. To realize these plans is good to know the evolution of the integration process of our country into the European Union. In this material the author is trying to highlight the way of Moldova's integration into the European family, making use in such a way of legislation adopted over two decades by the executive and representative and bodies.